2018
DOI: 10.1038/s41598-018-32859-4
|View full text |Cite
|
Sign up to set email alerts
|

A systems-approach reveals human nestin is an endothelial-enriched, angiogenesis-independent intermediate filament protein

Abstract: The intermediate filament protein nestin is expressed during embryonic development, but considered largely restricted to areas of regeneration in the adult. Here, we perform a body-wide transcriptome and protein-profiling analysis to reveal that nestin is constitutively, and highly-selectively, expressed in adult human endothelial cells (EC), independent of proliferative status. Correspondingly, we demonstrate that it is not a marker for tumour EC in multiple malignancy types. Imaging of EC from different vasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 95 publications
(109 reference statements)
3
11
0
Order By: Relevance
“…1B, all measured markers were expressed. The co-localized expression of pluripotency transcription factor Oct-4 with Nestin an intermediate filament of stem or progenitor cells [23] as well as the expression of the gap junction protein Connexin-43 [24,25] as a postulated marker for pre-migratory and migratory neural crest stem cells with the stage-specific embryonic antigen-4 (SSEA-4) a glycosphingolipid marker commonly known to be expressed in pluripotent cells which is downregulated through differentiation [26], supported the hypothesis of an immature stem cell population present in the hair follicle tissue region. This was further confirmed by the co-localized expression of CD34 with CD49f, which have been shown to be key modulators of HFSC identity in vitro [27].…”
Section: Tissue Characterizationmentioning
confidence: 99%
“…1B, all measured markers were expressed. The co-localized expression of pluripotency transcription factor Oct-4 with Nestin an intermediate filament of stem or progenitor cells [23] as well as the expression of the gap junction protein Connexin-43 [24,25] as a postulated marker for pre-migratory and migratory neural crest stem cells with the stage-specific embryonic antigen-4 (SSEA-4) a glycosphingolipid marker commonly known to be expressed in pluripotent cells which is downregulated through differentiation [26], supported the hypothesis of an immature stem cell population present in the hair follicle tissue region. This was further confirmed by the co-localized expression of CD34 with CD49f, which have been shown to be key modulators of HFSC identity in vitro [27].…”
Section: Tissue Characterizationmentioning
confidence: 99%
“…Despite a consistent number of observations in animal models, NESTIN expression is still poorly investigated in humans. Dusart et al (2018) recently reported data from transcriptome and antibody-based analysis of tissue microarrays (TMA) form adult human organs. This study revealed body-wide NESTIN expression in the ECs, both in normal and tumor tissues, independently from their proliferative status and debating the idea of NESTIN as neo-vascularization associated marker ( Suzuki et al, 2010 ; Matsuda et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, they reported high expression of Nestin in EC across several organs among them was the breast, challenging the previous knowledge of the restricted expression and stemness of Nestin. Furthermore, they observed a lower expression of Nestin in EC of bladder urothelial carcinoma and lung adenocarcinoma tissue than in corresponding normal tissue, further demonstrating that Nestin is not associated specifically with EC of tumors (15).…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, a recent study found a positive correlation between Nestin mRNA and Nestin protein expression in germline BRCA1 related breast cancer, a basal-like phenotype, with reduced survival, and stem ness characteristics (14). The marker expression was reported in endothelial cells of breast as well (15). So far, Nestin has been evaluated in breast cancer patients only on a tissue level using an immunohistochemistry technique for diagnostic and prognostication purposes.…”
Section: Introductionmentioning
confidence: 99%